Українські археологічні терміни в публікаціях 20–30-х років XX ст. - Локайчук, Світлана; Lokaіchuk, Svіtlana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті на матеріалі публікацій 20–30-х років ХХ ст. простежено особливості термінотворення в українській рхеологічній науці цього періоду. Проаналізовано процес формування лексико-тематичних груп та шляхи поповнення терміносистеми на етапі її становлення. Відображено стан і проблеми розвитку термінології досліджуваного періоду в українській науковій мові загалом. The article on the material articles 20 and 30 of the twentieth century. traced the features of terms in Ukrainian archaeological science of this period, analyzes the process of formation of lexical and thematic groups. Ways to refill terminological stages of development: active terminologization common words, making the timing by using the Ukrainian language word-building resources, selection Ukrainian counterparts to foreign language equivalent names using internationalism. Despite the lack of a critical editorial work on the selection of expressive means for scientific concepts, terminology had archaeological features of the system. The analysis shows the status and problems of terminology in the period studied Ukrainian scientific language in general.
Ukrainian Archaeological Terms in Publications 20–30 of the Twentieth Century
Keywords: археологічна термінологія; мова науки; термінотворення; тематична група; варіантність; archaeological terminology; the language of science; terminology; thematic group; variability